Women in the Synodal Church - Ann Mary Madavanakkad (Asian Horizons, 2025)
There is a growing awareness among us today that women are not given their rightful place in the life and mission of the Church. This exclusion has been often justified by recourse to Scripture. It is generally accepted that reading Scripture is ideologically biased against women, and some texts are mistranslated and misinterpreted by the exegetes. Hence, the Bible has become an important source and legitimizer for excluding and alienating women from the mission of the Church.